Causes, classification, diagnostics and treatment of hydrocephalus - Vjeran Saratlić; Vesna Ivanišević (Биомедицинска истраживања, 2019)
Hydrocephalus is a hydrodynamic disorder of the cerebrospinal cortex causing an enlargement of the ventricular system and increased pressure around the brain. Hydrocephalus can be divided into congenital and acquired, and, based on occurrence mechanism, into communicative (non-obstructive) and non-communicative (obstructive which can be congenital and acquired). There is also normal-pressure hydrocephalus, hydrocephalus ex vacuo, and external hydrocephalus in newborns. In newborns and infants, the main diagnosis method is the head ultrasound, through fontanels. After fontanel closure, diagnosis is established by means of magnetic resonance imaging (MR) and computed tomography (CT). Significant domination of obstructive hydrocephalus over the other types of it has been established in a sample of patients with hydrocephalus treated at Department of Neurosurgery of the Clinical Center of Banja Luka in a two-year period.
Keywords: cerebrospinal fluid; hydrocephalus; classification; CT and MRI diagnostics; treatment